“Why Haven’t I Tried Twitter Until Now?”: Using Twitter in Teacher Education (LEARNing Landscapes, 2018)
As teacher educators, we have used Twitter with the goal of jumpstarting the professional learning networks and teacher identity development of students in our courses and programs. Our use of Twitter has evolved over time and can inform the work of other teacher educators. In this article, we offer examples of the benefits of incorporating Twitter in teacher education. We describe some of the common challenges we have experienced at our two institutions and across multiple semesters of use. Based on our collective experiences, we offer recommendations to others who are using or are considering using Twitter with preservice teachers.
Keywords: social media; teacher identity; professional learning network; preservice teachers; technology